Gingival crevicular fluid levels of human beta‐defensin‐2 and cathelicidin in smoker and non‐smoker patients: a cross‐sectional study. (31st May 2013) - Ertugrul, A. S.; Sahin, H.; Dikilitas, A.; Alpaslan, N. Z.; Bozoğlan, A.; Tekin, Y.
<x xml:space="preserve">Abstract</x> Background and Objective Cathelicidin (LL‐37) and human β‐defensin‐2 (hBD‐2) are antimicrobial peptides that have additional functions in innate immunity. The purpose of this study was to evaluate LL‐37 and hBD‐2 levels in the following patient groups: non‐smoker patients with gingivitis (G), smoker patients with gingivitis (SG), non‐smoker patients with generalized aggressive periodontitis (AgP) and smoker patients with generalized aggressive periodontitis (SAgP). Material and Methods A total of 80 patients, including 20 G, 20 SG, 20 AgP and 20 SAgP were enrolled in the study. Clinical periodontal parameters, including periodontal status were assessed by measuring bleeding on probing, plaque index, gingival index, probing depth and clinical attachment loss. Enzyme‐linked immunosorbent assays were done to quantify LL‐37 and hBD‐2 levels in gingival crevicular fluid. Results Clinical periodontal parameters were found to have no statistically significant differences between the SAgP and AgP groups or between the SG and G groups. LL‐37 and hBD‐2 levels were significantly lower in G patients than in other groups. LL‐37 and hBD‐2 levels in the gingival crevicular fluid of SAgP patients were significantly higher than in other groups. LL‐37 and hBD‐2 levels in SG patients were also significantly higher than in G patients. Conclusions Epithelial cells in contact with microorganisms release LL‐37 and hBD‐2 to eliminate them. The release response of LL‐37 and hBD‐2 formed against microorganisms can change depending on factors such as smoking, which activates the nicotinic receptors present on epithelial surfaces. This interaction can increase the release of LL‐37 and hBD‐2. Smoking may also affect the capillary tissues and reduce leukocytic chemotaxis. The increased number of colonized microorganisms may lead to higher levels of LL‐37 and hBD‐2 release in the tissues of smokers than in non‐smokers.